Peningkatan Kapasitas Petani Closed-Loop Pangan (Beras) di Nusa Tenggara Timur - Nia Kurniawati Hidayat; Muhammad Firdaus; Tanti Novianti (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Capacity Development of Closed-Loop Food (Rice) Farmers in East Nusa Tenggara is a training that is carried out to increase the understanding of prospective farmers who implement the food closed-loop system (rice) in Nagekeo East Nusa Tenggara regarding the bookkeeping, access to financing and marketing. The training was held in Mbay, Nagekeo Regency. Participants are 14 partner farmers of Pandawa Agri Indonesia (PAI) who are currently or have implemented PAI Innovation. Activities are implemented in several stages from coordination, training, FGD, pre-test and post-test. Primary and secondary data were obtained and analyzed descriptively, quantitatively and qualitatively. There was an increase in farmers' knowledge about farming bookkeeping, access to financing and marketing strategies. Farmers are made aware of the importance of carrying out business bookkeeping and the essential steps for taking advantage of various agricultural financing schemes. Farmers also realized the importance of institutions, and together, the group determines targets, segments and current market positions for better marketing strategy design.